PENGARUH SENAM HAMIL TERHADAP NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III - Yuni Cahyani; Hasni Rahmah (Jurnal Ilmiah Citra Kebidanan, 2026)
Low back pain is a common complaint experienced by women in the third trimester of pregnancy due to physiological, biomechanical, and hormonal changes occurring during pregnancy. This condition can interfere with daily activities and reduce the quality of life of pregnant women if not properly managed. One safe and recommended non-pharmacological intervention to alleviate this complaint is pregnancy exercise. This study aimed to determine the effect of pregnancy exercise on reducing low back pain intensity among third-trimester pregnant women. This study employed a quantitative method with a pre-experimental one-group pretest–posttest design. The research was conducted at PMB Midwife Yuni Cahyani, Cianjur Regency, from November to December 2025. A total of 32 third-trimester pregnant women were recruited using a total sampling technique. The intensity of low back pain was measured using the Numeric Rating Scale (NRS) before and after the pregnancy exercise intervention. Data were analyzed using the Wilcoxon test. The results showed that the mean low back pain intensity decreased from 5.78 before the intervention to 4.25 after the intervention, with a p-value of 0.000 (p < 0.05). These findings indicate that pregnancy exercise has a significant effect on reducing low back pain intensity in third-trimester pregnant women. Therefore, pregnancy exercise is recommended to be integrated into antenatal care services as a non-pharmacological intervention to improve comfort and quality of life for pregnant women.